Histories of Migrants and Refugees in Australia. Issue 3 (3rd July 2018) - Balint, Ruth; Simic, Zora
Abstract : This article canvasses recent scholarship on migrants and refugees in Australian history. It covers broadly three main fields of enquiry: White Australia, postwar immigration and refugees since the Vietnam War. We argue there is a new dynamism to the field while simultaneously making the case that migrant and refugee history has hitherto been largely quarantined from mainstream Australian historiography.